2017
DOI: 10.1002/aenm.201700286
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Structural Dynamics on the Optical Properties of Methylammonium Lead Iodide Perovskites

Abstract: structure, [2] and changing the ratio of precursor compounds prior to the formation of the perovskite layer. [3] These approaches are based on modifying the crystallization process, for example, by controlling the composition of the precursor solution and by varying processing parameters. Such changes also led to major improvements in perovskite-based light-emitting devices within the last year. Initially, the current efficiencies were improved by optimizing the grain size to values below 100 nm, and by chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 101 publications
(246 reference statements)
7
59
0
Order By: Relevance
“…The laser power has been optimized for fast acquisition and as low as possible introduced power. We note, that the laser excitation power may play an important role in PL quantum efficiency and dynamics . Wang et al, for example, found a photo‐driven transformation in CsPbX 3 nanostructures.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…The laser power has been optimized for fast acquisition and as low as possible introduced power. We note, that the laser excitation power may play an important role in PL quantum efficiency and dynamics . Wang et al, for example, found a photo‐driven transformation in CsPbX 3 nanostructures.…”
mentioning
confidence: 77%
“…Wang et al, for example, found a photo‐driven transformation in CsPbX 3 nanostructures. Xing et al observed a decreased activation energy for ion migration under light illumination and the presence of migrating ions has direct implications on slow dynamic optical processes in perovskite‐based devices as has been recently reviewed by Panzer et al…”
mentioning
confidence: 94%
“…[ 47 ] Based on temperature‐dependent PL measurements and comparison with associated lattice constants, it is possible to estimate the strain that would be necessary to shift the PL by 20 meV to higher energies via the Birch‐Murnaghan‐equation. [ 48 ] With the assumption that lattice dilation is the dominant factor for the temperature‐dependent shift of the PL maximum, [ 6,12 ] we find tensile strain values of 85–165 MPa (see Section S7 in the Supporting Information for details). However, recent studies demonstrated that the unit cell volume of the orthorhombic phase is smaller than the one of the tetragonal phase, [ 4,45,49,50 ] and thus there should be compressive strain instead of tensile strain to affect the tetragonal inclusions.…”
Section: Discussionmentioning
confidence: 98%
“…For thin films, typically a large temperature range of 20–40 K can be observed in which both phases coexist. [ 4,10,12,41,42 ] This is argued to be caused by the polycrystalline nature of those films, where every grain can have a slightly different transition temperature, depending, e.g., on the grain size, [ 43 ] or the strain induced by the substrate. [ 10,11,44 ] In powders, the temperature range of the coexistence was reported to be smaller with 5–12 K, [ 10,45 ] which is likely due to the absence of substrate‐induced stress on the lose particles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation